A comprehensive review on biomass humification: Recent advances in pathways, challenges, new applications, and perspectives. (December 2022) - Wei, Shuxia; Li, Zichen; Sun, Yong; Zhang, Jiemei; Ge, Yuanyuan; Li, Zhili
Abstract: Humic acids (HAs) are natural organic polymers that are widely distributed in terrestrial soils, natural water, and sediments. Due to their excellent physical and chemical properties, HAs have outstanding commercial value and are used in a wide range of applications. However, the molecular structure of HAs is still unclear and is affected by different sources, time, and environment. Moreover, the extraction of HAs from lignite can no longer meet its current market demand. Therefore, the preparation of HAs from reserve-rich biomass is a promising strategy to add value to biomass. Herein, we comprehensively review the current status of research on HAs, from formation theory to structural properties and potential applications. In particular, artificial humification methods of biomass, including aerobic composting, catalytic/oxidation, and hydrothermal technology are highlighted. Nowadays, the mainstream technologies for biomass waste humification processes in the available reported work is composting and hydrothermal technologies. The highest yields of HAs produced until now by composting and hydrothermal technology were 94.97 g/kg and 43.5%, respectively. Among these, the hydrothermal method is considered a novel accelerated humification technology, synthesizing HAs up to the standard of commercial HAs. Finally, the problems of synthetic HAs technology are summarized and future development has prospected. To the best of our knowledge, this is the first detailed review of the preparation of HAs from biomass materials by biotic and abiotic conversion. Graphical abstract: Image 1 Highlights: The formation mechanism, structure, and properties of HAs are reviewed. The synthesis process and mechanism of HAs were systematically introduced. The effect of critical factors on biomass humification is summarized. Recent advances in potential applications of HAs are discussed. Foreseeable challenges and prospects in biotic and abiotic humification are proposed.